Pengaruh Rasio Keuangan Dan Good Corporate Governance Terhadap Risiko Pembiayaan Pada Bank Syariah - Nursaidah ,; Sugiyarti Fatma Laela (JRAK: Journal of Accounting Research and Computerized Accounting, 2022)
The purpose of this study is to examine the impact of financial ratios and good corporate governance on financing risk in Islamic banks. This study uses data from Islamic banks recorded in the Indonesian Financial Services Authority in 2012-2016. This study applies panel data regression method. The results found that the Board of Commissioners' independence has a negative effect on financing risk. In addition, financing to deposit ratio and operating expenses to operating income ratio have a positive effect on financing risk. While capital adequacy and effectiveness of audit committee do not affect financing risk.